A smart current modulation scheme for harmonic reduction in three-phase motor drive applications - Davari, P.; Zare, Firuz; Blaabjerg, F. (2015)
© 2015 EPE Association and IEEE. Electric motor-driven systems consume considerable amount of the global electricity. Majority of three-phase motor drives are equipped with conventional diode rectifier and passive harmonic mitigation, being witnessed as the main source in generating input current harmonics. While many active harmonic mitigation methods have been developed over the years, the total cost and complexity has become the main obstacle in employing prior-art methods for motor drive systems. This paper presents a novel current modulation method based on the electronic inductor concept for three-phase ac-dc systems to reduce input current harmonics. The obtained results at simulation and experimental levels confirm the effectiveness of the proposed approach.